Leaves and roots metabolomic signatures underlying rootstock-mediated water stress tolerance in grafted pepper plants - Yaiza Gara Padilla; Begoña Miras-Moreno; Ramón Gisbert-Mullor; Luigi Lucini; Salvador López-Galarza; Ángeles Calatayud (Plant Stress, 2024)
Grafting onto pepper rootstock NIBER® is an effective strategy to mitigate water stress effects on the grafted variety. In this work, we comparatively explored the metabolomic responses to water stress in the pepper variety “Maestral F1” (V) grafted onto NIBER® (V/N) and self-grafted (V/V) by untargeted metabolomics on leaves and roots. Leaf water status was also evaluated by relative water content (RWC) and gas exchange measurements. Under water stress, the V/N water use efficiency (WUE) and leaf RWC were higher than V/V, in agreement with major stomata closure and water retention in leaves. V/N showed a tolerance response, which was manifested in the untargeted metabolomic analysis. NIBER® modulated the grafted variety response to water stress as reflected in the differential metabolomic profiles in leaves and roots. The V/N-enriched metabolic pathways showed that the NIBER® response to water stress involved cutin and suberin biosynthesis, which act as protection layers, and jasmonic acid (JA) and jasmonates biosynthesis to favor signaling pathways. NIBER® did not induce flavonols and chlorophyll b synthesis, but likely promoted anthocyanins biosynthesis and maintained an undisturbed chlorophyll a:chlorophyll b ratio. Moreover, NIBER® increased vitamin B6, anthocyanins and stearic acid concentration in the variety leaves, whereas siroheme content rose in roots to improve nitrogen assimilation. Further studies are required to understand the contribution of secondary metabolites, such as phenylpropanoids, glycoalkaloids, and nitrogen-containing secondary metabolites, to NIBER® water stress tolerance.